Governança da água na Amazônia paraense: uma análise no uso da outorga de direito de uso dos recursos hídricos - MAIA, Paulo Cesar Chagas (Instituto Brasileiro de Informação em Ciência e Tecnologia, 2022)
The paper analyses how the grant (outorga) is a relevant tool for decision-making in the institutional process of water territories’ governance. In the context of social and institutional transformations, the water’s use, typology and purpose are emphasized by hydrographic region in Pará state. Theoretically, the research took into account the literatures of water governance, integrated water resources management and water resources right granting. Methodologically, the research was based on a quantitative and qualitative case study. A documental analysis was carried out on the texts produced by the Secretary of State for the Environment and Sustainability (SEMAS), particularly environmental management reports, state list of grants and State Water Resources Plan (products and diagnostics), accessed from the Pará State Water Resources Management System (SEGRH) and the Pará State Water Resources Information System (SEIRH/PA). The paper shows that the grant (outorga) is a relevant legal tool for environmental conservation. Accordingly, its use limits, values and rationalizes the sustainable water’s use in the territory and brings great benefits to the enterprises and local environmental public management. Through this instrument, it was possible to identify and spatialize the number of large enterprises that most use the grant in the state, with emphasis on groundwater drilling, disciplining its regulation in the hydrographic regions, subsidizing the process of governance, planning and management of territories of water.